2021
DOI: 10.1111/cpr.13145
|View full text |Cite
|
Sign up to set email alerts
|

MNSFβ regulates placental development by conjugating IGF2BP2 to enhance trophoblast cell invasiveness

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The placentas from Cyp27a1 HT mat and Cyp27a1 KO mat fetuses appeared normal (Figure 7A); however, their diameters and weights were significantly smaller than those from WT mothers (Figures 7B and C). Furthermore, histological analyses using H&E staining and immunostaining for cytokeratin 7 (CK7) (Yang et al, 2021) revealed that the labyrinth area of the placentas of Cyp27a1 KO mat fetuses was significantly thinner than that of Cyp27a1 HT mat and WT fetuses (Figures 7D-F), as reported in the Fau -deficient mice (Gu et al, 2015; Yang et al, 2021). Similar to that in the fetal lung, polysome formation in the placenta of Cyp27a1 KO mat fetuses was impaired (Figure 7G), suggesting an abnormality in translation.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…The placentas from Cyp27a1 HT mat and Cyp27a1 KO mat fetuses appeared normal (Figure 7A); however, their diameters and weights were significantly smaller than those from WT mothers (Figures 7B and C). Furthermore, histological analyses using H&E staining and immunostaining for cytokeratin 7 (CK7) (Yang et al, 2021) revealed that the labyrinth area of the placentas of Cyp27a1 KO mat fetuses was significantly thinner than that of Cyp27a1 HT mat and WT fetuses (Figures 7D-F), as reported in the Fau -deficient mice (Gu et al, 2015; Yang et al, 2021). Similar to that in the fetal lung, polysome formation in the placenta of Cyp27a1 KO mat fetuses was impaired (Figure 7G), suggesting an abnormality in translation.…”
Section: Resultsmentioning
confidence: 65%
“…Fau/Mnsfβ is highly and broadly expressed in both murine and human placenta, and Fau -deficient mice exhibit placental malformation (Gu et al, 2015; Yang et al, 2021). Moreover, a large cohort study has identified a single nucleotide polymorphism (SNP) in FAU to correlate with recurrent pregnancy loss in a Chinese Han population (Gu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RPS-30 UbL is a ubiquitin-like protein and its homologue in human functions in various biological processes by covalently binding to various target proteins, such as pro-apoptotic protein Bcl-G, phagocytosis-regulated protein endophilin II and invasion-related protein IGF2BP2. 18,19,41,42 The structure of 'beta folding grip' and the internal lysine residues, K27 and K43 in RPS-30 UbL ing Bcl-G, 18 which is a member of the Bcl-2 family of apoptosis control protein. 19 Therefore, with both the function and the structural characterization of potential modification, RPS-30 UbL might be related to the process of apoptosis induced by contaminants via accumulating to form the 'rod-like' structures.…”
Section: Discussionmentioning
confidence: 99%
“…RPS‐30 UbL is a ubiquitin‐like protein and its homologue in human functions in various biological processes by covalently binding to various target proteins, such as pro‐apoptotic protein Bcl‐G, phagocytosis‐regulated protein endophilin II and invasion‐related protein IGF2BP2 18,19,41,42 . The structure of ‘beta folding grip’ and the internal lysine residues, K27 and K43 in RPS‐30 UbL might indicate its function in ubiquitin‐like modification and the formation of the poly‐ubiquitin chain.…”
Section: Discussionmentioning
confidence: 99%